Technologies for children - Fleer , Marilyn (Australia : Cambridge, 2016)
Technologies for Children explores how traditional technologies can be repurposed and re-imagined in educational environments to engage students in interactive and authentic ways. Closely aligned with both the Australian Curriculum: Technologies and the Early Years Learning Framework, it covers theory and provides practical ideas for teaching infants, toddlers, pre-schoolers and primary school children. Each chapter focuses on different aspects of technologies education, such as engineering principles and systems, food and fibre, creativity in design, and preferred futures. Fully updated, the text features critical exploration of research in the field. Student learning is supported throughout by research activities and real-world example. The new edition is an indispensable resource for both pre-service teachers and practitioners. Drawing on over twenty-five years of experience, Marilyn Fleer presents clear approaches that are readily applicable in the classroom and equips students with the necessary skills and knowledge for teaching design and technology education in Australia.
Includes references and index.
Keywords: Technology -- Study and teaching -- Australia; Educational technology -- Australia; Education -- Philosophy